The predictive role of ultrasound-detected tenosynovitis and joint synovitis for flare in patients with rheumatoid arthritis in stable remission. Results of an Italian multicentre study of the Italian Society for Rheumatology Group for Ultrasound: the STARTER study. Issue 9 (9th June 2018) - Filippou, Georgios; Sakellariou, Garifallia; Scirè, Carlo Alberto; Carrara, Greta; Rumi, Federica; Bellis, Emanuela; Adinolfi, Antonella; Batticciotto, Alberto; Bortoluzzi, Alessandra; Cagnotto, Giovanni; Caprioli, Marta; Canzoni, Marco; et al.
Abstract : Objective: To define the role of ultrasound (US) for the assessment of patients with rheumatoid arthritis (RA) in clinical remission, including joint and tendon evaluation. Methods: A multicentre longitudinal study has been promoted by the US Study Group of the Italian Society for Rheumatology. 25 Italian centres participated, enrolling consecutive patients with RA in clinical remission. All patients underwent complete clinical assessment (demographic data, disease characteristics, laboratory exams, clinical assessment of 28 joints and patient/physician-reported outcomes) and Power Doppler (PD) US evaluation of wrist, metacarpalphalangeal joints, proximal interphalangeal joints and synovial tendons of the hands and wrists at enrolment, 6 and 12 months. The association between clinical and US variables with flare, disability and radiographic progression was evaluated by univariable and adjusted logistic regression models. Results: 361 patients were enrolled, the mean age was 56.20 (±13.31) years and 261 were women, with a mean disease duration of 9.75 (±8.07) years. In the 12 months follow-up, 98/326 (30.1%) patients presented a disease flare. The concurrent presence of PD positive tenosynovitis and joint synovitis predicted disease flare, with an OR (95% CI) of 2.75 (1.45 to 5.20) in crude analyses and 2.09 (1.06 to 4.13) in adjusted analyses. US variables did not predict the worsening of function or radiographic progression. US was able to predict flare at 12 months but not at 6 months. Conclusions: PD positivity in tendons and joints is an independent risk factor of flare in patients with RA in clinical remission. Musculoskeletal ultrasound evaluation is a valuable tool to monitor and help decision making in patients with RA in clinical remission.